Rock physics and geomechanics in the study of reservoirs and repositories - David, C.; Le Ravalec, Mickaële (Geological Society special publication ;, 2007)
The study of reservoir and repository performance requires the integration of many different fields in Earth sciences, among them rock physics and geomechanics. The aim of this book is to emphasize how rock physics and geomechanics help to get a better insight into important issues linked to reservoir management for exploitation of natural resources, and to repository safety assessment for hazardous waste storage in geological environment.